Penerapan Model Blended Learning Berbasis Video Youtube untuk Meningkatkan Kemampuan Literasi Matematis dan Kemandirian Belajar Siswa - Ramadhani; Rosdiana (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
This research aims to enhance students' mathematical literacy and self-regulated learning abilities by implementing video-based YouTube blended learning. The study utilized a quasi-experimental design with a pretest-posttest approach. Two classes, namely the experimental and control groups, were involved in this research. The study population consisted of all eighth-grade students at SMP Negeri 23 Medan, comprising six classes without special classes. Sampling was conducted randomly using the simple random sampling method. The experimental group consisted of 27 students from class VIII-C, while the control group consisted of 27 students from class VIII-A. The research instruments used included essay tests and questionnaires. Based on the data analysis and research findings, the significance value for mathematical literacy was 0.008, and for self-regulated learning was 0.000. As both probability values were less than 5%, the null hypothesis (H0) was rejected. This result indicates that implementing video-based YouTube blended learning improved students' mathematical literacy and self-regulated learning abilities at SMP Negeri 23 Medan.